Homogeneous Biocatalysis in Organic Solvents and Water-Organic Mixtures - Castro, Guillermo Raul (2003)
Biocatalysis in non-aqueous media has undergone tremendous development during the last decade, and numerous reactions have been introduced and optimized for synthetic applications. In contrast to aqueous enzymology, biotransformations in organic solvents offer unique industrially attractive advantages, such as: drastic changes in the enantioselectivity of the reaction, the reversal of the thermodynamic equilibrium of hydrolysis reactions, suppression of water-dependent side reactions, and resistance to bacterial contamination. Currently, the field is dominated by heterogeneous biocatalysis based primarily on lyophilized enzyme powders, cross-linked crystals, and enzymes immobilized on inert supports that are mainly applied in enantioselective synthesis. However, low reaction rates are an inherent problem of the heterogeneous biocatalysis, while the homogeneous systems have the advantage that the elimination of diffusional barriers of substrates and products between organic and water phases results in an increase in the reaction rate. Here the discussion is focused on the correlation between activity and structure of the intact enzymes dissolved in neat organic solvents, as well as modifications of natural enzymes, which make them soluble and catalytically active in non-aqueous environment. Factors that influence conformation and stability of the enzymes are also discussed. Current developments in non-aqueous biocatalysts that combine advantages of protein modification and immobilization, i.e. HIP plastics, enzyme chips, ionic liquids, are characterized. Finally, engineering enzymes for biotransformations in non-conventional media by directed evolution is summarized.